Tirani Meritokrasi dan Reimajinasi Solidaritas: Sebuah Kajian Berdasarkan Perspektif Michael Sandel - Petrus Tan (Jurnal Ledalero, 2023)
This article presents Michael Sandel’s concept on the tyranny of meritocracy and reimagining of solidarity and itsrelevance in Indonesia. Meritocracy is a kind of ideology that believes that those who are successful deserve tobreathe their success to their heart’s content, while for those who fail, there is no one to blame but themselves.Sandel’s view is that this logic makes meritocracy undermines togetherness and solidarity as the ethical foundationof democracy. The more we think that our success is our own effort, and the poor people’s failure as their own fault,it is harder for us to imagine ourselves in someone else’s shoes. Meritocracy makes liberal society accepts as fairthe hierarchy between the rich and the poor, the smart and the stupid, or the successful and the unsuccessful. Thisbelief generates arrogance for the winners and contempt for the losers. For Sandel, Trump’s populism in the US is aform of rebellion against the tyranny of meritocracy. To counter the tyranny of meritocracy and cultivate theimagination of solidarity, we should propose the idea of humility as a public virtue. Humility is an acknowledgmentthat all our talents, achievements, and success are not the results of our own efforts but rather it depends on theresources of the community and society that accepts these talents and abilities.Keywords: Meritocracy, Solidarity, Liberalism, Community, Humility.